Deconstructive Philosophy of Asylum: Matter of Hostipitality - IŞIKLI, ŞEVKİ (MARMARA UNIV, FAC COMMUNICATION, 2015)
This article aims at applying Derrida's views displayed in his work Hostipitality to the issues of asylum and refugee and also providing an exposition of the asylum's philosophy by this way. In the text, in addition to taking into consideration the translation indicated in the deepnote , texts that discusses Derrida's views on deconstruction in the context of ethics and politics are also referred to and hospitality's linguistic practices in the local culture (Turkish culture) such as aphorisms and proverbs are revealed as short texts. The exploration held illustrates that the matter of asylum and refugee is neither ethical nor political nor cultural, on the contrary it is the probability amplitude (or state vector) which includes more than their collecitons. When resolved through deconstructive techniques, being a refugee, which starts with seeking asylum, seems to include both linguistic and political apoiras. In order to overcome refugeeism as a problem, the aporias of binary/oppositional thinking should be perceived, totally-originally different thinking should be appealed within the multi-valued logical thinking and it should initiate thinking the unthinkable as Derrida suggests by abandoning the system thought. The small linguistic difference between hospitality and hostility pointed out by Derrida invites to re-think on the presence of hostility supperessed in the concept of hospitality, and invites to reconsideration those who are dealing with especially the matters of asylum and refugeeism, migration and policy of migration, ends and universality and even those known as hospitable. The main question whose answer is sought in all of them is as such: Is hospitality possible?
Keywords: Hospitality; Hostipitality; Asylum; Refugee; Derrida; Deconstruction; Philosophy of Refugeeism